2017
DOI: 10.1589/jpts.29.1737
|View full text |Cite
|
Sign up to set email alerts
|

Change in hand dexterity and habitual gait speed reflects cognitive decline over time in healthy older adults: a longitudinal study

Abstract: Abstract. [Purpose] There is a relationship between physical and cognitive functions; therefore, impairment of physical function would mean cognitive decline. This study aimed to investigate the association between change in physical and cognitive functions. [Subjects and Methods] Participants were 169 healthy community-dwelling older adults who attend the survey after three years from baseline (mean age, 72.4 ± 4.8 years). Grip strength, one-leg standing balance, five-times-sit-to-stand test, timed up and go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 22 publications
2
25
2
Order By: Relevance
“…However, we did not find significant correlations between MMSE and most of the examined physical performance measurements. This is in contrast to the many studies that have reported significant correlations between cognitive function and aspects of physical performance, such as HGS [12,13], QS [7], and walking speed [5,26]. These conflicting results may be explained by the fact that these previous studies included participants with various degrees of physical performance ability, whereas the present study evaluated only participants who were able to walk independently and therefore had a relatively high level of physical performance.…”
Section: Discussioncontrasting
confidence: 89%
See 4 more Smart Citations
“…However, we did not find significant correlations between MMSE and most of the examined physical performance measurements. This is in contrast to the many studies that have reported significant correlations between cognitive function and aspects of physical performance, such as HGS [12,13], QS [7], and walking speed [5,26]. These conflicting results may be explained by the fact that these previous studies included participants with various degrees of physical performance ability, whereas the present study evaluated only participants who were able to walk independently and therefore had a relatively high level of physical performance.…”
Section: Discussioncontrasting
confidence: 89%
“…The most important contribution of this study was the simultaneous evaluation of seven physical performance measures among Japanese men aged 80 years or older who were able to walk independently, revealing the reference values for these measures in this study population. Following previous studies, we also evaluated the correlations between cognitive function and physical performance [5,7,8,[11][12][13] and between age and physical performance [6,[9][10][11]. To the best of our knowledge, the present study is the first to examine correlations among multiple physical performance measures, finding various levels of correlation.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations